PETIC Decision Making (PDM) : um modelo automatizado para apoio à tomada de decisão estratégica em TIC - Rocha, Fabio Gomes (2017)
Strategic planning is essential for the management of Information and Communication Technologies in organizations, providing more assertive decisions to establish the basic purposes of improvement and implementation of new resources. The goal of this study was the adaptation of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in the creation of a new model to support decision making on the prioritization of investments in strategic planning of Information and Communication Technologies as a support to the methodology PETIC, called PETIC Decision Make (PDM), evaluating its applicability in real case studies. The investigated institutions were a municipal public administration body and a labor union entity, where the PDM was used in the prioritization of investments for the period of five years, using the tool PDMSys created in this study. By means of the proposed method was possible to select alternatives of actions considered preferable and to analyze their dependencies, besides creating a continuous cycle for classification. The results indicated the practicability of the method, avoiding an indication that the dependencies would jeopardize the investment in technologies. In this way, it was verified that the application of the PDM increases the predictability of expenditures, allows the reduction of initial costs and contributes to the assertiveness in the decisions on the management of the technological resources, implying in the global management of the institutions.